Weather warning system in Hungary and the experiences of its operation - Sallai Buránszki, Márta; Horváth, Ákos (Hungarian Geographical Bulletin, 2014)
Extreme environmental events may have catastrophic impacts on the society. Almost 90% of all natural disasters of the last 10 years have been caused by weather related hazards, i.e. floods, droughts, tropical cyclones and severe storms. The basic task of meteorology is to provide weather forecasts and warnings for public welfare to protect life and property. The weather warning system was set up by the Hungarian Meteorological Service (HMS) in 2006. The first system was capable to provide warnings and alerts for the 7 administrative regions of the country. In 2011 as a result of scientific and methodological development and infrastructural investment, financed by a competition support, the old system was replaced with a sub-regional weather warning system providing weather warnings towards the public, the disaster management and other decision-makers for 174 administrative sub-regions instead of the former seven regions. The first part of this paper provides an overview of the scientific and operational background of the nowcasting system. Then the two years' experiences of its operation will be reviewed. Finally, the problems caused by people's attitude to various weather situations and weather information will be discussed, together with some recommendations to improve the human factor of our professional efforts.